2012
DOI: 10.1179/2045772311y.0000000042
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in paediatric patients with spina bifida

Abstract: The prevalence and morbidity associated with osteoporosis and fractures in patients with spina bifida (SB) highlight the importance of osteoporosis prevention and treatment in early childhood; however, the issue has received little attention. The method for the selection of appropriate patients for drug treatment has not been clarified. Objective: To review the literature concerning fracture risks and low bone density in paediatric patients with SB. We looked for studies describing state-of-the-art treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 85 publications
(154 reference statements)
0
23
0
1
Order By: Relevance
“…Current techniques for measuring BMD rely most commonly on dual-energy x-ray absorptiometry (DXA) and, to a lesser extent, peripheral quantitative computed tomography (pQCT). DXA provides a projected areal measure of BMD and therefore cannot provide a complete adjustment for bone size [5]. This limitation has consequences for comparing BMD across individuals of different physical sizes [68], including children with spina bifida who typically have short stature in comparison to typically developing peers [9].…”
Section: Introductionmentioning
confidence: 99%
“…Current techniques for measuring BMD rely most commonly on dual-energy x-ray absorptiometry (DXA) and, to a lesser extent, peripheral quantitative computed tomography (pQCT). DXA provides a projected areal measure of BMD and therefore cannot provide a complete adjustment for bone size [5]. This limitation has consequences for comparing BMD across individuals of different physical sizes [68], including children with spina bifida who typically have short stature in comparison to typically developing peers [9].…”
Section: Introductionmentioning
confidence: 99%
“…However this time; during postoperative rehabilitation that applied to the patient without prediction of low bone quality, patient had femur fracture twice in a short period. In this case we especially aimed to emphasize this complication should be in our mind in these group of patients with poor bone quality and sensory deficits (4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 93%
“…In these group of patients fractures can be seen because of the low bone density, lower extremity atrophy and some other osseous problems can be seen because of less usage of extremity in a percent of 11 -30 % (4)(5)(6)(7)(8). The fractures don't seen as frequent as urologic and neurologic complications but it is very comfortless for the patient (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disuse osteoporosis occurs in patients suffering from spinal cord injury [Alizadeh‐Meghrazi et al, 2014] or spina bifida [Marreiros et al, ] and is also observed in patients with bedridden condition due to neuronal and cardiovascular diseases [Jaul et al, ]. Osteoporosis during space flight has been another major issue in addition to the pathological conditions on the ground levels [Leblanc et al, ].…”
Section: Discussionmentioning
confidence: 99%